Students' Perception on Blended Learning in English Class during the COVID-19 Pandemic: English - Putri Indah Sari; Erni Erni; Rumiri Aruan (Prodi Tadris Bahasa Inggris, 2023)
The improbability of continuing the traditional classroom during the pandemic Covid-19 caused an Unavoidable condition where blended learning was the most proper solution to conduct the learning process. This study intends to investigate how students view blended learning, particularly in English classrooms. The research's population is the eighth-grade students of MTS Fadhilah Pekanbaru with 93 students involved as the research samples. The instrument used to gain the data is a questionnaire consisting of 35 items divided into four aspects (behavioral, cognitive, emotional, and economic). The data were scored using a Likert scale with four options; Strongly Agree (SA), Agree (A), Disagree (D), and Strongly Disagree (SD). The findings showed that the students’ perception on blended learning was high level with an average score of 107.46. Owing to this, it can be determined that the students had positive perceptions when learning English through a blended learning method. They showed positive behaviors during blended learning where they always came to the lessons and submitted their assignments on time. Also, they believed blended learning allowed them to explore their potential and be more creative in the learning process.